Evaluation of possible error sources in corneal endothelial morphometry with a semiautomated noncontact specular microscope - Doughty, Michael J (Cornea, 2013)
To assess the corneal endothelium, particularly the polymegethism feature, using the Topcon SP-3000P specular microscope with newer center-dot software. Forty-eight healthy, normal weight, noncontact lens wearers of Asian ethnicity were assessed. Single endothelial images from each subject were processed with center-dot software, reevaluated after correction of obvious errors, and then by manual border marking and planimetry. Endothelial cell density based on average cell area and the coefficient of variation (COV) of cell area (polymegethism) were calculated. Error sources are associated with erroneous location of cell borders (usually creating larger or smaller "cells") or failure to assign cell borders to a marked cell. On the initial application of the center-dot software, the endothelial cell density values ranged from 1822 to 3244 cells per square millimeter (mean, 2644 cells/mm); this range was reduced (eg, 1955-3054 cells/mm; mean 2690 cells/mm on editing or in manual planimetry). The COV values ranged from 17% to 39% (mean, 27.5% ± 5.5%), with one third of the endothelia yielding COV values of greater than or equal to 30%. On editing or in manual planimetry, the COV values were reduced to between 17% and 29% (mean, 24.5% ± 3.2%; P < 0.001). In the use of a center-dot endothelial analysis program with cell border identification, it is likely that at least 1 set of editing steps is required to produce reasonable results.